How do academic libraries work with their users to co-create value for service innovation?: A qualitative survey - Islam, Anwarul; Agarwal, Naresh Kumar; Ikeda, Mitsuru (Qualitative and Quantitative Methods in Libraries, 2017)
Libraries today face continual challenges from rising costs and shrinking budgets to demand for new types of services. If libraries are to meet these challenges and to successfully innovate, they must not only provide value to the user unidirectionally, but must work together with the user for service innovation. However, co-creation and innovation studies are rare in libraries. Islam, Agarwal and Ikeda (2015a) proposed a value co-creation framework for service innovation in academic libraries. In this study, we empirically test the framework.  Open-ended web-based questions were sent by email to heads of libraries and other librarians. 21 respondents answered the questions based on their perceptions on value co-creation and service innovation practices in their libraries. Findings show that academic libraries work with users to co-create value in areas such as project management, makerspaces, information literacy, design of library websites, etc. Despite some concerns, most respondents saw value co-creation as critical to the innovation of new services and the continuing success of their library. The study sheds light on the importance of value co-creation for service innovation in academic libraries, and contributes to literature in this emerging research area of service science.